"We learnt lots in a short time": Cultural exchange across three universities through songs from different lands. (May 2020) - Joseph, Dawn; Nethsinghe, Rohan; Cabedo-Mas, Alberto
Establishing strong connections between universities within initial teacher education (ITE) programs not only takes time, but it also presents opportunities and challenges. Tertiary music educators are called to prepare ITE students/pre-service teachers to be culturally responsive. This article forms part of our wider study "See, Listen and Share: Exploring Intercultural Music Education in a Transnational Experience Across Three Universities (Royal Melbourne Institute of Technology University, Australia; Deakin University, Australia; and Universitat Jaume I of Castelló, Spain). For this article, we draw on student web survey data, anecdotal feedback, and our reflections. We employ Interpretative Phenomenological Analysis as a tool to thematically group our surveys into three broad overarching themes to inform our findings and discussions. We argue that music education is an effective vehicle for exploring culture and diversity through song. Our findings show that our ITE students built positive attitudes about using songs in their generalist primary and early childhood classrooms. They also recognized the importance of collaborative sharing using face-to-face and Skype. This project proved a worthy experience for all concerned, it formed a rich part of our professional learning. We encourage others to consider the approach as one way to promote multicultural music and cultural diversity within ITE programs and across other educational settings.